Comparison of Phenotypic and Genotypic Identification Methods of Pasteurella multocida Serotypes Isolated from Pigs - Amaral, Amanda Figueiredo; Rebelatto, Raquel; Klein, Catia Silene; Takeuti, Karine Ludwig; Barcellos, David Emilio Santos Neves de (Acta Scientiae Veterinariae, 2016)
Background: Pasteurella multocida serotypes A and D are commonly associated with pneumonia and pleuritis in pigs. Different phenotypic techniques, such as hyaluronidase and acriflavine tests, and genotyping techniques, such as PCR, are used to distinguish between these serotypes. The objective of this study was to compare the capsular identification methods of type A and type D P. multocida isolated from pigs using both phenotypic (hyaluronidase and acriflavine tests) and genotypic (multiplex PCR) techniques. Materials, Methods & Results: A total of 44 lyophilized P. multocida isolates, obtained between 1981 and 1997 from pig farms at Rio Grande do Sul State, Brazil, were analyzed. The isolates were reactivated in Brain Heart Infusion (BHI) broth and cultured in BHI broth and blood agar supplemented with 5% sheep blood. Colony identity was further confirmed by evaluating colony morphology in blood agar and confirming the absence of growth on MacConkey agar. Bacteria in Tryptone Soy Agar (TSA) were used for the Triple Sugar Iron (TSI), Sulfide-Indole-Motility (SIM), and nitrate, glucose, lactose, sucrose and mannitol fermentation tests. For hyaluronidase test, P. multocida colonies were streaked transversally across the entire plate, approximately 3-5mm apart, in order to observe their lines of growth. Following this, a hyaluronidase producing strain of Staphylococcus aureus was heavily streaked at right angles to the P. multocida lines and the plates were incubated at 37°C for 24 h. Type A isolates were then identified as those with smaller colonies in the region adjacent to the Staphylococcus aureus streak (negative satellitism). For acriflavine test, the isolates were inoculated into tubes containing 2 mL of BHI, incubated at 37°C for 18-24 h, centrifuged (500 g for 15 min) and 1.5 mL of the supernatant was discarded. A 1:1000 solution of acriflavine neutral (0.5 mL) was then added to the residual broth containing bacteria and kept at room temperature. Solutions of acriflavine were freshly prepared each week and stored protected from light. Type D strains were identified by the appearance of a heavy flocculent precipitate within 5 min. DNA extraction by heat shock was performed prior to multiplex PCR for the detection of capsular genes hyaD-hyaC (capsular typing A) and dcbF (capsular typing D). Test of symmetry and a weighted kappa coefficient were used to evaluate correlations and to assess agreement of the results between the identification methods, respectively. Phenotypic tests showed that two isolates were type D (4.55%), 40 were type A (90.9%) and two (4.55%) were untypable isolates (4.55%) while PCR showed that 38 isolates were type A (86.36%) and six were type D (13.64%). The correlation analysis between the phenotypic and genotypic tests showed that 90.9% of the strains were identified as belonging to the same serotype by both tests and the weighted kappa coefficient (K = 0.633) indicates a substantial agreement between the two tests. Discussion: There was a disagreement between the phenotypic and genotypic results in four of the isolates (9.09%). The phenotypically untypable isolates were classified as type D by multiplex PCR. Nonetheless, we conclude that PCR testing is a more reliable method to differentiate between P. multocida serotypes A and D.